Lipsome-coated metal organic frameworks as a new drug nanocarrier - Mohamed, Omnia A. (2019)
A Master of Science thesis in Biomedical Engineering by Omnia A. Mohamed entitled, “Lipsome-coated metal organic frameworks as a new drug nanocarrier”, submitted in December 2019. Thesis advisor is Dr. Rana Sabouni and thesis co-advisor is Dr. Ghaleb Husseini. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).